Evaluasi Digital Adherence Technology Berbasis Kode QR (Q-Monte) untuk Pemantauan Kepatuhan Pengobatan Tuberkulosis - Farid Zulkarnain Nur Syah; Noor Annisa Susanto; Akhmad Zainuri (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2026)
Tuberculosis (TB) treatment adherence is a critical determinant of therapeutic success; however, monitoring adherence remains challenging in primary healthcare settings. Digital adherence technology (DAT) offers an alternative approach to monitor patient adherence more efficiently. This study aimed to evaluate the initial feasibility of implementing a QR code–based DAT system (Q-Monte) for monitoring TB treatment adherence in primary healthcare centers. This study employed a pilot feasibility design with a prospective observational approach involving 30 outpatient TB patients from two primary healthcare centers in Malang Regency. Participants were recruited using purposive sampling with the following inclusion criteria: TB patients aged ≥12 years, receiving oral anti-tuberculosis therapy, owning an Android-based smartphone and an active WhatsApp number, and being willing to be monitored for 30 days. Patients with HIV co-infection or multidrug-resistant TB (TB-MDR), those who transferred healthcare facilities during the observation period, or those with stroke comorbidity were excluded. Most participants were male (56.7%), aged 45–54 years (30.0%), had completed senior high school education (50.0%), and had no comorbidities (80.0%). Adherence was measured as the percentage of days with QR code scanning, while system usability was assessed using the System Usability Scale (SUS). The results showed an average QR code scanning adherence rate of 90.3% over 30 days, with 46.7% of patients reporting having taken medication without performing the QR code scan. The usability evaluation yielded a mean SUS score of 75.7 (grade B). These findings indicate that Q-Monte is feasible as a tool for monitoring TB treatment adherence in primary healthcare settings, although further optimization of technical support and user education is needed to improve the reliability of digital adherence recording.